Philosophies of adoption:perspectives and reflections - Cassidy, Lisa; Lotz, Mianna (2024)
Philosophies of Adoption: Perspectives and Reflections explores philosophical analysis of adoption, providing insight into new and underexplored topics in the field. Three scholarly developments are central to the emerging philosophical discourse on adoption explored in this volume: a problematizing of the adoption triangle or “triad", a critique of the so-called “bio-normative" family, and an attention to specific issues in transracial and First Nations adoption. The book’s contributors expand on all three of these areas by addressing a range of questions—How does being adopted shape self-knowledge and identity? What challenges arise at the intersection of race and adoption? What can be learned about epistemic justice, identity, and belonging from transracial adoption? What are the narratives told about adoption?—to show how current conditions and lived adoptee experiences give new shape, meaning, and importance to philosophical thinking about adoption. Showcasing a range of styles, this book provides first-hand accounts of adult-adoptees through diverse standpoints, voices, perspectives, and relationships to adoption.